Efficacy and safety of fondaparinux versus enoxaparin in patients undergoing percutaneous coronary intervention treated with the glycoprotein IIb/IIIa inhibitor tirofiban - Zhao, Xin (Mil Med Res, 2016)
BACKGROUND: In worldwide, the mortality rate of acute myocardial infarction (AMI) raises year by year. Although the applications of percutaneous coronary intervention (PCI) and anticoagulants effectively reduce the mortality of patients with acute coronary syndrome (ACS), but also increase the incidence of bleeding. Therefore, drugs with stable anticoagulant effects are urgently required. METHODS: We enrolled 894 patients with acute coronary syndrome who underwent percutaneous coronary intervention in Shenyang Northern Hospital from February 2010 to May 2012; 430 patients were included in the fondaparinux group (2.5 mg/d), and 464 were included in the enoxaparin group (1 mg/kg twice daily). Fondaparinux and enoxaparin were applied for 3–7 days. All patients were treated with tirofiban (10 μg/kg for 3 min initially and 0.15 μg/(kg · min) for 1 to 3 days thereafter). The primary efficacy endpoint was the incidence of a major adverse cerebrovascular or cardiovascular event. The primary safety endpoint was bleeding within 30 days and 1 year after percutaneous coronary intervention. RESULTS: One-year data were available for 422 patients in the fondaparinux group and for 453 in the enoxaparin group. The incidence of a major adverse cerebrovascular or cardiovascular event (10.9 % vs 12.6 %, P = 0.433) and cardiac mortality (0.5 % vs 1.5 %, P = 0.116) were generally lower in the fondaparinux group than in the enoxaparin group, although the differences were not significant. Compared with the enoxaparin group, the fondaparinux group had a significantly decreased rate of bleeding at 30 days (0.9 % vs 2.8 %) and 1 year (2.4 % vs 5.4 %). In addition, the rate of major bleeding events was lower in the fondaparinux group, but this difference was not significant (0.2 % vs 0.9 %, 0.2 % vs 1.1 %). CONCLUSIONS: In tirofiban-treated patients with acute coronary syndrome undergoing percutaneous coronary intervention, fondaparinux presented similar efficacy for ischemia events as enoxaparin. However, fondaparinux significantly decreased the incidence of bleeding, thus providing safer anticoagulation therapy.